MicroRNA-582-3p knockdown alleviates non-alcoholic steatohepatitis by altering the gut microbiota composition and moderating TMBIM1 - Huang, Shuo; Xiao, Xia; Wu, Hongman; Zhou, Feng; Fu, Chenchao (Irish journal of medical science, 2024)
Background The gut dysbiosis correlates with non-alcoholic steatohepatitis (NASH), involving the moderation of miRNAs. Aims This study was aimed to investigate the correlation between gut microbiota and miR-582-3p in patients with non-alcoholic steatohepatitis (NASH) and to explore the possible regulation of miR-582-3p in the function of the activated hepatic stellate cells (HSCs). Methods GSE69670 and GSE14435 datasets were analyzed by GEO2R. Plasma and fecal samples were obtained from the subjects, non-steatosis ( n = 35), simple steatosis ( n = 35), and NASH ( n = 35). The variations in intestinal microbiota in the non-steatosis and NASH groups were analyzed using 16S rRNA sequencing. The expression of miR-582-3p among the groups was detected using RT-qPCR. Correlations between top-changed intestinal microbiota and miR-582-3p expression were analyzed using the Pearson correlation coefficient. Target gene identification was performed by prediction and dual-luciferase reporter assay. The effect of miR‐582-3p on the cell function of TGF-β1-induced HSCs was assessed in vitro. Results miR-582-3p was the common differentially expressed miRNA between GSE69670 and GSE14435. miR-582-3p was upregulated in NASH patients’ plasma, as well as in TGF-β1-induced LX-2 cells. The non-steatosis and NASH groups showed significantly different intestinal microbiota distribution. miR-582-3p was positively correlated with specific microbiota populations. TMBIM1 was a target gene for miR-582-3p. Knockdown of miR-582-3p suppressed HSC proliferation and myofibroblast markers’ expression but induced cell apoptosis, via TMBIM1. Conclusions This present study suggests that miR-582-3p promotes the progression of NASH. Knockdown of miR-582-3p may alleviate NASH by altering the gut microbiota composition and moderating TMBIM1.